China's fiscal decentralization and environmental quality: theory and an empirical study. (2nd April 2020) - Hao, Yu; Chen, Yu-Fu; Liao, Hua; Wei, Yi-Ming
Abstract: As a wide-reaching institutional reform, China's fiscal decentralization was launched in the early 1980s to encourage provincial economic growth by granting more financial autonomy to provincial governments. In this paper, the impact of fiscal decentralization on China's environmental quality is investigated both theoretically and empirically. A neoclassical model is developed based on the primary characteristics of China's fiscal decentralization. Using provincial panel data for the period 1995-2015, a two-equation regression model is employed to empirically verify the three propositions of the theoretical model: (1) there exists an inverted-U shaped relationship between fiscal decentralization and GDP per capita; (2) fiscal decentralization is positively related to GDP per capita at the steady state; (3) there is an inverted-U shaped Environmental Kuznets Curve relationship between pollution emissions and economic growth.